Penambahan Karagenan Dalam Edible Coating Lidah Buaya (Aloe vera. L) untuk Mempertahankan Kualitas Tomat Selama Penyimpanan - Yunisa, Fina; Zalfiatri, Yelmira; Dewi, Yossi Kharisma (JURNAL AGROINDUSTRI HALAL, 2025)
The aim of this study was to obtain the best concentration of carrageenan in aloe vera edible coating on the quality of tomatoes during storage. This research was carried out experimentally using a completely randomized design (CRD) with five treatments and three replications. The edible coating treatments included K0 (without carrageenan), K1 (0.3% carrageenan), K2 (0.4% carrageenan), K3 (0.5% carrageenan), and K4 (0.6% carrageenan) which were applied to tomatoes during 16 days of storage. Sidik variance showed that the addition of carrageenan to aloe vera edible coating had a significant effect on the analysis of milk weight, hardness, total dissolved solids, vitamin C content, and descriptive color and texture tests. The best treatment in this study was aloe vera edible coating with the addition of 0.6% carrageenan (K4) in maintaining the quality of tomatoes during the 16th day of storage, with a weight loss value of 4.90%, hardness of 7.69 kg/f, total solids dissolved 1.47 ºBrix, vitamin C 21.65 mg/100g. The sensory assessment of tomatoes in the K4 treatment descriptively had a score of 4.73 (reddish orange), texture with a score of 3.83 (hard texture).